THE EFFECT OF SHADING AND SPRAYING SALICYLIC ACID INRECIPES VEGETATIVEE GROWTH OFTHE TOMATO PLINT Lycopersicon esculentum Mill MANNER VERTICAI TRAINING METHOD - Kh. , Yasser Y.; H. , Zakaria H.; Al-Hamdani, Sabeeh A. (Diyala Agricultural Sciences Journal, 2018)
An experiment was done by design Complete Randomized sectors RCBD experiment carried out in the Dept. of Horticulture- Faculty of Agric., University of Diyala during Spring season 2015, to study the impact of global shading and spraying of Salicylic acid on some recipes vegetative growth of tomato crop. It included three shading levels (without shading 0% , 35% and 65%) and four concentrations of Salicylic acid (0 , 75, 150, 225 mg gm-1) splashed on the first two installments after month and the second two months after planting seedlings to study plant height, leaf area, stem diameter, number of leaves, and the percentage of dry matter. The differences between the averages was tested by a polynomial Duncan at 0.05 level of significance. The results showed that increasing shading treatment at level 65% caused a significant increase in plant height, while this treatment led to obtain a significant decrease in the average number of leaves and the average stem diameter per plant compared to shading 35% and 0%, while the treatment of shading level 35% caused moral superiority in leaf area and the percentage of dry matter. While spraying of Salicylic acid resulted a superiority of moral qualities of the plant and leaf area, the length and number of leaves and the percentage of dry matter in leaves. Treatments did not differ in the stem diameter. While there were significant differences between some overlap interactions in all traits.